Aportaciones a la arquitectura señorial leonesa nuevos datos sobre el palacio de Villasinda - Campos Sánchez-Bordona, María Dolores, 1949-, (Estudios humanísticos. Geografía, historia y arte, 1999)
The Villasinda palace of the town of León, represets one of the best example of the seignorial architecture of the Modem Age at Spain. The building was done during the XVI and XVII centuries, with the style of the architectonic clasicism, and destined as the house of the Quirós Quiñones Beaumont's noblie family. In 1907, it was burned, and the central part at the front and the interior were destroyed. The architec Juan C. Torbado rebuilt it again in 1908.